THE ELDERLY IN THE WORLD OF WORK: CURRENT CONFIGURATIONS - Cláudia Maria da Silva Sá; Norma Valéria Dantas de Oliveira Souza; Célia Pereira Caldas; Marcia Tereza Luz Lisboa; Kelly Fernanda Assis Tavares (Universidade Federal do Paraná, 2011)
This bibliographic research, of qualitative and descriptive character, aimed to study the elderly in the world of work. The objective was to analyze the psychosocial impacts on the elderly caused by their remaining or re-entering the workforce. The bibliographic search was undertaken between May and August 2010, via the databases LILACS, SciELO, BDENF and MEDLINE. Nine research articles were found. Discussion of the information was structured around the categories The relationship between the world of work and the elderly person and The psychosocial situation of the Elderly. The phenomenon of elderly people remaining in or re-entering the workforce is tending to increase and, therefore, a re-planning of public policies regarding the phenomenon is necessary. It was ascertained that this thematic must be investigated in its many dimensions and that a fresh look at organization and conditions of work is urgently needed, so as to guarantee health and safety to the elderly worker.